The Supreme Court and McCarthy-era repression : one hundred decisions - Lichtman, Robert M., 1933- (Urbana : University of Illinois Press, 2017)
In this volume, attorney Robert M. Lichtman provides a comprehensive history of the US Supreme Court's decisions in 'Communist' cases during the McCarthy era. Lichtman shows the Court's vulnerability to public criticism and attacks by the elected branches during periods of political repression.
Previously issued in print: 2012.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 13, 2017).
Keywords: United States. -- Supreme Court -- History -- 20th century; Civil rights -- United States -- Cases; United States -- Politics and government -- 1945-1989.; Law; United States of America, USA; History; Constitutional & administrative law: general